1991
DOI: 10.1073/pnas.88.10.4404
|View full text |Cite
|
Sign up to set email alerts
|

The ligand specificities of the insulin receptor and the insulin-like growth factor I receptor reside in different regions of a common binding site.

Abstract: To identify the region(s) of the insulin receptor and the insulin-like growth factor I (IGF-I) receptor responsible for ligand specificity (high-affinity binding), expression vectors encoding soluble chimeric insulin/IGF-I receptors were prepared. The chimeric receptors were expressed in mammalian cells and partially purified. Binding studies revealed that a construct comprising an IGF-I receptor in which the 68 N-terminal amino acids of the insulin receptor a-subunit had replaced the equivalent IGF-I receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 34 publications
9
90
1
Order By: Relevance
“…The concentration of insulin needed to observe this effect corresponds to high physiologic serum levels around 0.15 nM (31) and increased at concentrations of ≥1.5 nM, which are present in patients treated with high doses of insulin or analogs (31)(32)(33). It seems reasonable that the high concentrations of human insulin studied are needed to elicit this growth effect, because affinity of insulin for its receptor is two to three orders of magnitude higher than for the cognate IGF-1 receptor (30). The efficient silencing of the IR [which has a half life of ~6-12 h (34,35)] through blocking its synthesis by a 3-day antisense knockdown, as well as the lack of an effect of IR-neutralizing antibodies, make involvement of the IR in this novel effect of insulin unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of insulin needed to observe this effect corresponds to high physiologic serum levels around 0.15 nM (31) and increased at concentrations of ≥1.5 nM, which are present in patients treated with high doses of insulin or analogs (31)(32)(33). It seems reasonable that the high concentrations of human insulin studied are needed to elicit this growth effect, because affinity of insulin for its receptor is two to three orders of magnitude higher than for the cognate IGF-1 receptor (30). The efficient silencing of the IR [which has a half life of ~6-12 h (34,35)] through blocking its synthesis by a 3-day antisense knockdown, as well as the lack of an effect of IR-neutralizing antibodies, make involvement of the IR in this novel effect of insulin unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…However, only stimulation with 30 nM glargine led to EPC outgrowth (186% ± 41%, P < 0.001) similar to that of human insulin (180% ± 33%, P < 0.001) (Figure 2c). The dosedependent effect of insulin on EPC outgrowth was observed between 0.15 and 15 nM, reflecting concentrations at which the IR is saturated (22,30). Therefore, we speculated that the effects are not mediated by the IR, and examined alternative receptors and signaling cascades involved in the increased outgrowth of EPCs upon stimulation with human insulin.…”
Section: Influence Of Human Insulin and Analogs On The Outgrowth Of Ementioning
confidence: 99%
“…Interestingly, substitution of Lys 65 and Lys 68 in the D region with Ala also reduced IGF-I receptor affinity approximately 10-fold, suggesting that multiple basic residues (Lys 27 , Arg Rutter [35] demonstrated that 56 and 52 amino acid stretches in the cysteine-rich regions of the insulin and IGF-I receptors, respectively, contained major determinants for ligand binding specificity. Others have confirmed the importance of the cysteine-rich region of the IGF-I receptor in ligand specificity [36][37][38], but have suggested that the N-terminal 68 amino acid portion of the insulin receptor a -subunit contains the key residues for insulin selectivity [38]. It is interesting to note that the C-terminal 20 amino acids of the region of the IGF-I receptor described by Gustafson and Rutter contains one basic residue and five acidic residues, which might interact with the essential basic residues on IGF-I.…”
Section: Discussionmentioning
confidence: 99%
“…Supraphysiological concentrations of insulin enhance adipose conversion of preadipose cell lines by acting through the IGF-1 receptor [215]. Cross-reactions with this receptor is indeed possible when insulin is added at high concentrations [45,140]. Because no or poor effects are observed with physiological concentrations, similar interpretation concerns human and rabbit preadipocytes [105,182].…”
Section: Insulin Igf-1 and Ghmentioning
confidence: 99%